Complete Blood Profile and Neutrophil-Lymphocyte Ratio of Electrical Stunning and Non-Stunning Swine - Bq Nurlita Anugrah; I Wayan Suardana; Hamong Suharsono (Institute for Research and Community Service, Udayana University, 2022)
Examination of the blood profile is crucial because blood functioned as an important role in the circulatory system and can be used to evaluate the emergence of stress in animals. The purposes of this research are to examine the complete blood profile and examine the possibility of stress symptoms by measuring the ratio of neutrophils-lymphocytes as the indicator of stress in electrical stunned and non-stunned swine. There were 40 six-month life swine with a weight of 80-100kg. The swine grouped into stunning and non-stunning group. A total of 3 ml of blood sample occupied and placed to a contained anticoagulant Ethylene Diamine Tetraacetic Acid (EDTA) vacutainer. The total of erythrocytes, hemoglobin, PCV, MCV, MCH, leukocytes and differential leukocytes were calculated using routine hematological examination methods with autoanalyzer machines. Based on the results of the research, the complete blood profile of electrical stunning slaughtered swine was healthier and more reliable than non-stunning. The ratio of neutrophils-lymphocytes in electrical stunning slaughtered swine was lower than non-stunning. This condition indicated a lesser amount of stress on the use of electric stunning.